THRIL mediates endothelial progenitor cells autophagy via AKT pathway and FUS - Jiandong Xiao; Yuli Lu; Xinchun Yang (BMC, 2020)
Abstract Background This study focused on the roles of lncRNA THRIL in coronary atherosclerotic heart disease (CAD) through regulating AKT signaling pathway and directly interacting with FUS. Methods QRT-PCR was conducted to detect the expression of THRIL in CAD blood samples and endothelial progenitor cells (EPCs). Cell autophagy of EPCs was examined through Cyto-ID Autophagy Detection Kit. CCK-8 assay and flow cytometry were carried out to assess cell viability and apoptosis under various interference conditions. Western blotting was conducted to detect the expression of interest proteins. The expression levels of vascular cell adhesion molecule-1 (VCAM-1) and intercellular adhesion molecule-1 (ICAM-1) were measured by qRT-PCR. The direct interactions between HCG18 and FUS was confirmed through RNA electrophoretic mobility shift assay (RNA EMSA) and RNA immunoprecipitation (RIP) assay. Results THRIL was upregulated in CAD blood samples and EPCs. Knockdown of THRIL in EPCs promoted cell viability, inhibited cell autophagy and further suppressed the development of CAD. Over-expression of THRIL induced inactivation of AKT pathway, while knockdown of THRIL played reversed effects. THRIL directly interacted with FUS protein and knockdown of FUS reversed the over-expressing effect of THRIL on cell proliferation, autophagy and the status of AKT pathway. Conclusion THRIL inhibits the proliferation and mediates autophagy of endothelial progenitor cells via AKT pathway and FUS.